Structure of therapy and compliance of patients with severe arterial hypertension - Aigerim Mussina; Raikhan Tuleutayeva; Natalya Cebotarenko; Matthias Hammerer; Assem Makhatova; Laura Pak (National Scientific Medical Center, 2017)
The purpose of the study was to determine the structure, compliance to antihypertensive pharmacotherapy in patients with arterial hypertension of the third degree in the conditions of Semey and the frequency of achieving target BP. The study included 618 patients with hypertension III degree. The age of patients ranged from 38 to 77 years (mean age - 61,2 ± 2,7 years). Among the surveyed men was -353, women - 265. Carried out an analysis of medical records and patient survey to determine the structure of antihypertensive therapy, compliance to it and the existing violations preparations reception mode. Was revealed prevalence in the appointment's structure the combinations of antihypertensive drugs (46.0%) and fixed combinations (29.0%). Monotherapy performed more frequently with beta-blockers and calcium channel antagonists. It revealed the greatest compliance to the use of fixed combinations of drugs and most high clinical efficacy of antihypertensive therapy options.